Absorption, metabolism, anti-cancer effect and molecular targets of epigallocatechin gallate (EGCG): An updated review - Gan, Ren-You; Li, Hua-Bin; Sui, Zhong-Quan; Corke, Harold (Critical reviews in food science and nutrition, 2018)
Green tea is one of the most popular beverages in the world, especially in Asian countries. Consumption of green tea has been demonstrated to possess many health benefits, which mainly attributed to the main bioactive compound epigallocatechin gallate (EGCG), a flavone-3-ol polyphenol, in green tea. EGCG is mainly absorbed in the intestine, and gut microbiota play a critical role in its metabolism prior to absorption. EGCG exhibits versatile bioactivities, with its anti-cancer effect most attracting due to the cancer preventive effect of green tea consumption, and a great number of studies intensively investigated its anti-cancer effect. In this review, we therefore, first stated the absorption and metabolism process of EGCG, and then summarized its anti-cancer effect in vitro and in vivo, including its manifold anti-cancer actions and mechanisms, especially its anti-cancer stem cell effect, and next highlighted its various molecular targets involved in cancer inhibition. Finally, the anti-cancer effect of EGCG analogs and nanoparticles, as well as the potential cancer promoting effect of EGCG were also discussed. Understanding of the absorption, metabolism, anti-cancer effect and molecular targets of EGCG can be of importance to better utilize it as a chemopreventive and chemotherapeutic agent.